2020
DOI: 10.1016/j.ijnsa.2020.100006
|View full text |Cite
|
Sign up to set email alerts
|

Nursing perspectives on care delivery during the early stages of the covid-19 pandemic: A qualitative study

Abstract: Background Research examining RNs’ experiences during the COVID-19 pandemic is lacking, thus inhibiting efforts to optimize nursing care delivery and patient outcomes during the current pandemic and future public health emergencies. Objective To explore the experience of being a registered nurse caring for patients with COVID-19 at an urban academic medical center during the early stages of the pandemic Design Qualitative descriptive study, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
173
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(190 citation statements)
references
References 18 publications
10
173
0
7
Order By: Relevance
“…The results of the current study had consistently shown that physical therapists also experienced similar emotions and feelings as other healthcare professionals, since fear was the most intense and long-lasting emotion in these professionals [ 14 , 28 , 36 ]. During the first COVID-19 outbreak, various types of fear have been identified [ 37 ]; (a) the fear of attendance at work (doctors and nurses avoid accepting patients in the hospital and staff avoid being back at the hospital), (b) fear of infection (concern about family and the virus), (c) fear of getting sick (themselves or their family), (d) fear of more COVID-19 waves, (e) fear of an increase in mortality (death of patients and colleagues, particularly medical colleagues’ death had a huge negative effect on health professionals). Ardebili et al [ 14 ] and Barello et al [ 28 ] showed that healthcare professionals who worked during the pandemic reported concerns regarding their fear of dying alone and being separated from their loved ones, fear of infecting their families, friends, or colleagues, and fear of stigmatization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current study had consistently shown that physical therapists also experienced similar emotions and feelings as other healthcare professionals, since fear was the most intense and long-lasting emotion in these professionals [ 14 , 28 , 36 ]. During the first COVID-19 outbreak, various types of fear have been identified [ 37 ]; (a) the fear of attendance at work (doctors and nurses avoid accepting patients in the hospital and staff avoid being back at the hospital), (b) fear of infection (concern about family and the virus), (c) fear of getting sick (themselves or their family), (d) fear of more COVID-19 waves, (e) fear of an increase in mortality (death of patients and colleagues, particularly medical colleagues’ death had a huge negative effect on health professionals). Ardebili et al [ 14 ] and Barello et al [ 28 ] showed that healthcare professionals who worked during the pandemic reported concerns regarding their fear of dying alone and being separated from their loved ones, fear of infecting their families, friends, or colleagues, and fear of stigmatization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported that healthcare professionals did not receive professional psychological support from their workplace centers during the first months of the acute COVID-19 outbreak [ 36 , 37 , 38 ]. In Spain, Martínez-López et al reported that 90% of the healthcare professionals considered that psychological care should have been provided from their workplace centers [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…• Ambiguity of information about COVID-19 (He et al 2020;Sadati et al 2020) • Far less information about patients' diagnosis when coming to the ED, except checking patients' fever (Hou et al 2020) • Excessive and rich source of information, but most of them were rumours and unclear (Pei et al 2020;Sadati et al 2020;Schroeder et al 2020;Yin & Zeng, 2020) • Sudden outbreak of the virus, still under investigation of the virus, its medications; thus, strong need for knowledge about the novel virus (Sheng et al 2020;Yin & Zeng, 2020) Unpredictable tasks and challenging practices…”
Section: Limited Information About Covid-19mentioning
confidence: 99%
“…• Hospital and healthcare system unprepared to care for COVID-19 patients (He et al 2020;Hou et al 2020;Pei et al 2020;Shen et al 2020) • Lack of protective facilities such as isolation units (Kackin et al 2020;Sadati et al 2020;Schroeder et al 2020;) • Limited equipment, such as PPE, for protecting healthcare practitioners (He et al 2020;Hou et al 2020;Sadati et al 2020) • Shortage of staff who care for infected patients (Kackin et al 2020;Zhang et al 2020) Concerns about family…”
Section: Limited Information About Covid-19mentioning
confidence: 99%
“…In hospitals, nursing staff were on the frontline providing care in close physical proximity to patients with COVID-19 and had direct risk of being exposed to the virus (Sim, 2020). Nurses worked long hours under extremely dynamic conditions, had heavy workloads, and carried the fear of becoming infected and transmitting the virus to family and friends (Liu et al, 2020; Schroeder et al, 2020). Many have experienced a decline in psychological well-being, such as increased anxiety, depression, and post-traumatic stress (Giusti et al, 2020), that may interfere with the safe delivery of high-quality care.…”
mentioning
confidence: 99%